Does the "like" habit of social networking services lower the psychological barriers to recommendation intention in surveys? - Takumi Kato (Business Systems Research (BSR), 2021)
Background: Companies often measure their customers' recommendation intention using the loyalty index based on the idea that a customer who has high loyalty and is committed to a brand has the confidence to recommend it to others. The psychological barrier is higher for recommendation intention, which may influence the behavior of others than for satisfaction on an individual level. However, the action of recommending has become commonplace due to the spread of social networking services (SNS). Pushing the "like" button for posts by family, friends, and co-workers has become an ingrained practice for consumers. Therefore, it is thought that "like" habits in SNS may lower the psychological barriers to the recommendation. Objectives: In this study, it was hypothesized that the more people habitually like posts on SNS, the higher the score for their recommendation intention in a customer survey. Methods/Approach: Propensity score matching was used to investigate a causal effect between the likes and the recommendation intention in a customer survey. Results: Based on the results of an online survey of chocolate brands in Japan, the causal effect was verified by propensity score matching. Conclusions: The results suggest that not only in companies but also in academic research, a valid concern is that the causal effect cannot be accurately evaluated unless a survey design is performed in consideration of the effects.
Keywords: M10; M31; 330; customer relationship management; loyalty; customer survey; social networking services